THE EFFECT OF QUIZLET LIVE MODE ON STUDENTS’ VOCABULARY MASTERY IN PROCEDURE TEXT - Azman Zakaria; Ikhsanudin Ikhsanudin; Eka Fajar Rahmani; Luwandi Suhartono; Sumarni Sumarni (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
This study aimed to investigate whether using Quizlet Live mode in Quizlet Application for ninth-grade students of SMPN 4 SAMBAS affected the students’ vocabulary mastery in procedure text. This study followed pre-experimental study using a pre-test and post-test with a single group design. The sample was IX C class students, consisting of 28 students that were taken through random cluster sampling. The analysis was carried out using both the pre- and post-test data, which were then analyzed using the t-test and effect size formulas. The finding showed that the t-test result was 16,36 and the t-table with a degree of freedom (df) 27 and a significance level of 0.05 was 2.052. This data showed that the t-test was higher than the t-table (16,36˃2.052). It demonstrated that the alternative hypothesis was accepted and the null hypothesis was declined. In addition, the treatment's effect size score was 2.83, which was regarded as a strong effect. Referring to the study's findings, it can be inferred that the utilization of Quizlet's live mode had a considerable effect on the students' vocabulary mastery in procedure text.